IDENTIFICATION AND ASSESSMENT OF OCCUPATIONAL SAFETY RISKS IN CASE OF FAILURE TO CAPTURE AN ORPHAN SOURCE OF IONIZING RADIATION - Tomek, Miroslav; Benčíková, Eleonóra; Strohmandl, Jan; Tomášek, Pavel (Journal of Applied Engineering Science, 2022)
Occupational safety and health belong to fundamental human rights. This fully applies to the protection of employees and other persons, which operate or are located in facilities for the collection of scrap metal. The founder of the landfill or the employer has an irreplaceable place in the field of protection of persons against the effects of ionizing radiation. Based on the identification and assessment of occupational safety risks in the event of failure to ensure timely detection of an orphan source of ionizing radiation, the operator must assess all risk factors with emphasis on radiation. At the same time, it must take specific regime measures, which would minimize the impact on people and the environment. The article deals with the causes of failure the system of protection against the effects of ionizing radiation. The assessment of these causes is performed using the fault tree analysis method with the application of Boolean equations. The result of solving the problem is the calculation of the failure of the regime protection system in the devices, intended for the collection of scrap metal, caused by human error as a result of intentional or negligent actions of the operator and insufficient training in the areas of control of measuring devices, principles of correct use of detection devices, insufficient visual identification of potentially dangerous objects. The contribution of this paper is in the design of appropriate regime measures eliminating the consequences of non–capturing a source of ionizing radiation.